Definition of manufacturability - product of mathematical expressions and fuzzy logic for his early design - Antic, Radivoje Borivoje; Cvetkovic, Slavica; Pejovic, Branko; Cvetkovic, Milan (International Journal of Engineering and Technology, 2013)
The paper explaines manufacturability of products for robust design of a new product. Explained mathematical expressions of fuzzy logics describe manufacturability. Provides an example of using the model for the determination of the tmanufacturability.